PYRETHROID RESISTANCE IN AEDES MOSQUITOES IN EAST KALIMANTAN, INDONESIA: SYSTEMATIC REVIEW 2005-2025 - Fitria Anggraini; Mona Zubaidah; Khairunnida Rahma; Shalvira Purnama (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Synthetic pyrethroid insecticides remain the primary vector control strategy for Aedes sp. mosquitoes, the principal vectors of dengue, Zika, and chikungunya (1). Understanding regional resistance patterns is crucial for effective vector management programs in endemic areas.Objective : To systematically review and synthesize evidence on pyrethroid insecticide resistance status in Aedes sp. populations in East Kalimantan Province, Indonesia, from 2005 to 2025.Research Methods : A systematic literature review was conducted following PRISMA 2020  guidelines (13). Multiple databases including PubMed, Scopus, Web of Science, Google Scholar, and Indonesian Publication Index were searched from January 2005 to October 2025. Studies reporting pyrethroid resistance in Aedes sp. from East Kalimantan were included. Data extraction followed PICO framework with quality assessment using modified Newcastle-Ottawa Scale.Results : Eight studies met inclusion criteria, encompassing 1,880 mosquitoes from multiple districts. Confirmed pyrethroid resistance was documented in Ae. aegypti populations across the province. Permethrin resistance ratios ranged from 4.08× to 127×, while deltamethrin resistance ranged from 4.37× to 72.20×. Mortality rates were 32.5-78.3% for permethrin and 41.7-82.1% for deltamethrin. High frequencies of kdr mutations (F1534C: 74.6%; V1016G: 69.2%) were detected, with 61.9%showing double mutations. Synergist assays demonstrated significant involvement of cytochrome P450 monooxygenases and esterases in resistance mechanisms.Conclusion : High-level pyrethroid resistance is widespread in Aedes aegypti populations throughout East Kalimantan Province, with both target-site and metabolic resistance mechanisms contributing to the phenotype. Current pyrethroid-based vector control strategies are likely compromised, necessitating urgent implementation of insecticide resistance management programs.